ANALYSIS OF SYMBOLS TRADITIONAL WEDDING OF NDUE URANAK IN TANIMBAR ISLAND REGENCY (SEMIOTIC STUDY) - Christina Rawung; Lisa Rosalina Mainake (REFORM : Jurnal Pendidikan, Sosial, dan Budaya, 2020)
The problem raised in this study is the meaning of symbols in the traditional Ndue Uranak wedding ceremony in the Tanimbar Island district using the semiotic study of Charles Sanders Peirce. This research is a type of qualitative research. Data was collected using the methods of documentation, interviews, recording, and note-taking techniques. The data analysis method in this study uses Charles Sanders Peirce's triangle theory of meaning which consists of icons, indexes, and symbols. The results of this study indicate that symbols in the ceremony In the traditional wedding ceremony there are several symbols that have their respective meanings such as the symbol of Lela (elephant tooth), Belusu (bracelet), Ngoras (neck necklace), Berun ampil (belt), Mas dedin (gold on the forehead), Sopi (alcohol drinks), Lelebutir (wedding property), Somalae (accessories on the head), etc. These symbols give rise to the meaning of a unified whole that the symbols are presented as a form of hope, the prayers of the Tanimbar people so that their sons and daughters who will build a household are always given sustenance, a life full of happiness. The ideal marriage in the Tanimbar community is a marriage that takes place outside of their respective clans and of the same religion. The organizer of this marriage is also to accelerate kinship relations, maintain the dignity of the clan and keep property from getting out of the hands of other people. The Ndue Uranak ceremony is one of the traditional marriage processions of the Tanimbar people which is still carried out by the Tanimbar people, especially in the Adault village. For the Tanimbar local government, it is hoped that this traditional cultural procession can be used as a cultural tourism destination.Keywords: Analysis, Tetun Language, Connotation Meaning.